2012
DOI: 10.21608/jaess.2012.45366
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality of Agricultural Extension Centers in Assiut Governorate Using Servperf Scale قیاس جودة الخدمة المقدمة من المراکز الإرشادیة الزراعیة بمحافظة أسیوط بإستخدام مقیاس Servperf

Abstract: The aim of this research is to measure and evaluate service quality of the agricultural extension centers in Assiut governorate using SERVPERF scale and its weighted version (importance-weighted SERVPERF). The study was conducted on 119 farmers distributed equally on the 17 extension centers of Assiut governorate. The results showed that although the respondents' overall view of the performance of service quality dimensions is high, the perceptions in all quality dimensions did not meet its maximum scores. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We have also found studies [68][69][70] using SERVPREF in the agricultural sector. These studies have shown relevance of the model in this industry and contributes to characterize customers, diagnose the perception of the level of quality of the services provided, and the requirements for improvement in service features so to satisfy the customer.…”
Section: Satisfaction and The Servperfmentioning
confidence: 58%
“…We have also found studies [68][69][70] using SERVPREF in the agricultural sector. These studies have shown relevance of the model in this industry and contributes to characterize customers, diagnose the perception of the level of quality of the services provided, and the requirements for improvement in service features so to satisfy the customer.…”
Section: Satisfaction and The Servperfmentioning
confidence: 58%